Pengembangan Media KUBIKAL Sebagai Sarana Pengenalan Konsep Dasar Perkalian di Kelas 2 Sekolah Dasar - Lathifah Eka Nur Maretha; Isrok'atun Isrok'atun; Ani Nur Aeni (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
The purpose of this study is to ascertain the processes involved in creating high-quality KUBIKAL learning materials for second-grade elementary school pupils studying mathematics through multiplication. The five stages of the ADDIE model which is analyze, design, develop, implement, and evaluate are used in this development research. 32 SDN Sukaraja 1 grade II students served as the study's test subjects. The present study employs various data collection techniques product validation sheets and including student response questionnaires. The researchers use these techniques to obtain data from product trials. With a percentage of 97% and the criteria is very good from material expert validators and 91.5% and the criteria is very good from media expert validators, the results demonstrated that KUBIKAL media is very feasible to use. The outcomes of the student's responses in the one-to-one trials which were carried out with 3 students got a percentage of 95.83% and the criteria were very good, the small group trials which were carried out with 8 students got criteria very good, then the field trials carried out with 21 students got criteria very good. So it can be concluded that KUBIKAL can be used by especially elementary school teachers because it's easy to use and the material on KUBIKAL is easy to understand.